The “Small Finds” through the photographic records on an archaeological excavation in Egypt at the beginning of the XXth Century: the case of the archives of James E. Quibell (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Going through the archives of James E. Quibell (1867-1935) on his excavations at Saqqara, which are kept at the University of Milan, this paper would query the approach in recording “small finds” held by an archaeologist working in Egypt at the beginning of the XXth Century.